PENENTUAN PENETRASI AIR DAN HIDROKARBON DARI KRISTAL CAIR LAMELAR DALAM SISTEM GARAM NITRAT, SIKLOHEKSANE DAN LAURIL ALKOHOL POLI ETER - Ali Amran (Jurnal Riset Kimia, 2010)
Abstract Water and hydrocarbon penetrations of the lamellar liquid crystal in nitrate salts (calcium and aluminium nitrates), cyclohexane, and lauryl alcohol polyether (LA4) system have been investigated. Liquid crystal phase which characterized using optical polarizing microscope and small-angle X-ray diffraction, showed  a significantly the water and the hydrocarbon penetrations of aluminium nitrate and calcium nitrate solutions.  Keywords: Lamellar liquid crystal, Optical polarizing microscope, Water and hydrocarbon penetration, Nitrate salts (calcium and aluminium nitrates), Lauryl alcohol polyether (LA4), Small-angle X-ray diffraction.